2012
DOI: 10.1182/blood-2011-10-386094
|View full text |Cite
|
Sign up to set email alerts
|

GFI1 and GFI1B control the loss of endothelial identity of hemogenic endothelium during hematopoietic commitment

Abstract: Recent studies have established that during embryonic development, hematopoietic progenitors and stem cells are generated from hemogenic endothelium precursors through a process termed endothelial to hematopoietic transition (EHT). The transcription factor RUNX1 is essential for this process, but its main downstream effectors remain largely unknown. Here, we report the identification of Gfi1 and Gfi1b as direct targets of RUNX1 and critical regulators of EHT. GFI1 and GFI1B are able to trigger, in the absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
181
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 157 publications
(200 citation statements)
references
References 51 publications
(83 reference statements)
13
181
0
1
Order By: Relevance
“…However, they were unable to generate hematopoietic colonies in vitro, something CD41 + cells isolated from wild type ES cell cultures or embryos readily do. In complementary experiments, the loss of both Gfi1 and Gfi1b resulted in the generation of CD41 expressing adherent cells that maintained endothelial marker expression, which could only generate clonogenic progeny upon disaggregation [80]. Altogether these data indicate that the Runx1 target genes, Gfi1 and Gfi1b may be in part responsible for the repression of endothelial gene expression associated with the early steps of EHT.…”
Section: Runx1mentioning
confidence: 87%
See 1 more Smart Citation
“…However, they were unable to generate hematopoietic colonies in vitro, something CD41 + cells isolated from wild type ES cell cultures or embryos readily do. In complementary experiments, the loss of both Gfi1 and Gfi1b resulted in the generation of CD41 expressing adherent cells that maintained endothelial marker expression, which could only generate clonogenic progeny upon disaggregation [80]. Altogether these data indicate that the Runx1 target genes, Gfi1 and Gfi1b may be in part responsible for the repression of endothelial gene expression associated with the early steps of EHT.…”
Section: Runx1mentioning
confidence: 87%
“…The first insights of these studies showed that Runx1 represses the endothelial program whilst activating the hematopoietic program (reviewed in [51]). More recently, the Runx1 target genes Gfi1/Gfi1b, but not Pu.1 (Sfpi1) or c-myb, were shown to down-regulate expression of endothelial genes in Runx1 null hemogenic endothelium derived from ES cells [80]. In addition, the Gfi1/Gfi1b transduced hemogenic endothelial cells initiated morphological changes akin to the formation of hematopoietic progeny, forming round cells that express CD41.…”
Section: Runx1mentioning
confidence: 99%
“…TALE-effectormediated PU.1 repression in a murine ESC differentiation confirmed the presence of PU.1 at sites of mouse definitive hematopoiesis [35]. However, using the same experimental model, Lancrin et al [36] investigated the capability of the major downstream targets of RUNX1, i.e., GFI1, GFI1B and PU.1, to rescue the defective phenotype of Runx1…”
Section: Identification and Cloning Of Runx1 And Spi1 (Pu1)mentioning
confidence: 99%
“…RUNX1 was shown to be essential for the formation of intra-aortic clusters, HSCs and hematopoietic progenitor formation [31], via facilitated expression of critical regulators of the EHT. These include GFI1 and GFIB, which trigger down-regulation of the endothelial markers Tek/ TIE2, VE-Cadherin/CDH5 and KIT, even in the absence of RUNX1 [36]. Genome-wide studies have shown that hematopoietic genes such as PU.1 are actually primed in the HE by occupancy of TAL1/SCL and FLI1 to their regulatory regions and that a RUNX1-mediated reorganization of these factors is critical during EHT [44].…”
Section: Developmental-stage-specific Runx1 and Pu1 Functionmentioning
confidence: 99%
“…It is now widely accepted that the hematopoietic transcription factor RUNX1 is a key master regulator of this process (Chen et al, 2009;Lancrin et al, 2009;Lie-A-Ling et al, 2014). RUNX1 is expressed in HE and emerging HSPCs both in the yolk sac and in the embryo proper (Frame et al, 2015;Lancrin et al, 2009;North et al, 1999), and controls the downregulation and upregulation of endothelial and hematopoietic transcriptional programs, respectively (Lancrin et al, 2012;Tanaka et al, 2012;Thambyrajah et al, 2016). RUNX1 has been shown to act in a heptad of interacting transcription factors in hematopoietic progenitor cells (HPCs) comprising FLI1, ERG, TAL1, LYL1, LMO2 and GATA2 (Wilson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%